Aceclofenac–β-cyclodextrin-vesicles: a dual carrier approach for skin with enhanced stability, efficacy and dermatokinetic profile. Issue 25 (19th February 2016) - Sharma, Gajanand; Kaur, Manmeet; Raza, Kaisar; Thakur, Kanika; Katare, O. P.
Abstract : The aim of the current investigation was to develop and characterize lipid-based carriers of aceclofenac (ACE) with enhanced stability and transdermal delivery potential to the inflammatory sites in osteoarthritis. Abstract : The aim of the current investigation was to develop and characterize lipid-based carriers of aceclofenac (ACE) with enhanced stability and transdermal delivery potential to the inflammatory sites in osteoarthritis. An attempt was made to complex the drug with a biocompatible complexing agent, i.e., β-cyclodextrin and the same was further encapsulated in the lipid bilayers of liposomes. FT-IR studies depicted the masking of one of the functional groups of ACE indicating the interaction of the drug–CD complex with the lipid bilayers of the prepared liposomes. The values of particle size, polydispersity index (PDI), zeta potential of the developed carrier system were found to be 481.7 nm, 0.214 and −29.54 mV, respectively. The system was further incorporated in a hydrogel which was found to be a shear-thinning system with a yield value of 3.625 Pa and viscosity of 3.085 Pa s. Skin permeation studies revealed the superiority of the prepared ACE loaded-β-CD liposomal gel over the MKT gel with an enhancement ratio of 2.69. Skin irritancy studies performed on LACA mice skin proved the safety and non-irritancy of the prepared formulation. The dermatokinetic studies confirmed better permeation and enhanced skin bioavailability of ACE to epidermis as well as dermis vis-à-vis the MKT product. The developed system not only improved the delivery aspects of ACE, but also offered substantial stability to this highly hydrolysis labile molecule. The current findings provide a lead for the development of an effective topical formulation of ACE with substantial stability in β-cyclodextrin-vesicles.